2010
DOI: 10.1002/jor.21110
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐biofilm activity of sub‐inhibitory povidone‐iodine concentrations against Staphylococcus epidermidis and Staphylococcus aureus

Abstract: Biomaterial-related infections continue to hamper the success of reconstructive and arthroplasty procedures in orthopaedic surgery. Staphylococci are the most common etiologic agents, with biofilm formation representing a major virulence factor. Biofilms increase bacterial resistance to antimicrobial agents and host immune responses. In staphylococci, production of polysaccharide intercellular adhesin (PIA) by the enzyme products of the icaADBC operon is the best understood mechanism of biofilm development, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 52 publications
3
52
1
2
Order By: Relevance
“…Hydroxypropyltrimethyl ammonium chloride chitosan inhibits biofilm formation as well as expression of the icaA gene (40). Providone iodine also inhibits biofilm formation and decreases transcription of the ica operon (38). The effects of natural antibacterial agents, such as berberine, carvacrol, farnesol, oregano, rhodomyrtone, and thymol, against staphylococcal biofilms have been frequently reported (24,37,47,54).…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxypropyltrimethyl ammonium chloride chitosan inhibits biofilm formation as well as expression of the icaA gene (40). Providone iodine also inhibits biofilm formation and decreases transcription of the ica operon (38). The effects of natural antibacterial agents, such as berberine, carvacrol, farnesol, oregano, rhodomyrtone, and thymol, against staphylococcal biofilms have been frequently reported (24,37,47,54).…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus epidermidis is a very common member of the human skin microbiota [53], and is thought to usually act as a mutualist, preventing pathogen colonization both directly by antibiotic production [54] and indirectly by 'priming' the immune system to deal with other microbes [53]. It is now recognized as a common and critically important cause of nosocomial infections [55]; the mutualism can become virulent pathogenesis when S. epidermidis gains access to internal tissues [53,56]. Similarly, the bacterium Parachlamydia acanthamoebae is normally an endosymbiont of the amoeba Acanthamoeba polyphaga, which inhabits the human nasal cavity.…”
Section: Context-dependent Symbioses Across Disciplines (A) Evolutionmentioning
confidence: 99%
“…In addition, although in vitr o studies have shown that both silver and iodine wound dressings have some ability to kill bacteria in biofilm, the body of evidence is inconsistent. 14–19 It is increasingly recognised that there remains a pressing need to reliably translate laboratory data into the clinical setting due to the potential impact of many clinical variables on sustained dressing antimicrobial action and availability. Fig 1a shows what is most likely to be the green pigment indicative of pyocyanin produced within a Pseudomonas aeruginosa biofilm growing on a metallic silver foam saturated with wound exudate.…”
mentioning
confidence: 99%